HUBUNGAN PEMBERIAN REWARD DAN PUNISHMENT DENGAN MOTIVASI BELAJAR PPKN PESERTA DIDIK KELAS V SDN 189 PEKANBARU - Nuramadina, Agilia; Ramadan, Zaka Hadikusuma (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to examine the significant relationship between the provision of rewards and punishments by teachers and the learning motivation of Civics Education (PPKn) students in grade V at SDN 189 Pekanbaru. This quantitative study employed a correlational design. The population consisted of 150 students, with 38 randomly selected as the sample. Data were collected using a Likert-scale questionnaire to measure the independent variable (rewards and punishments) and the dependent variable (learning motivation). Hypothesis testing was conducted using the Pearson correlation coefficient and the coefficient of determination. The results show a correlation coefficient of 0.517, categorized as moderate, and the significance test yielded a p-value of 0.001 < 0.05, indicating a positive relationship. These findings suggest that the use of rewards and punishments by teachers significantly contributes to enhancing PPKn learning motivation among grade V students at SDN 189 Pekanbaru.